Efficacy of three plant extracts in reducing sediment and heterotrophic bacterial load in surface raw water in Samburu District, Kenya. - Cheluget, Kipkemboi (Kabarak University, 2015)
Water quality changes associated with livestock production include changes in nutrients loads, (nitrogen and phosphorus), microorganisms (e.g. bacteria, faecal coliforms, Cryptosporidium, Giardia) and organic material such as livestock wastes
Keywords: Efficacy; three plant extracts; sediment and heterotrophic bacterial load; Samburu District, Kenya.